THE SIGNIFICANCE OF THE CORPORATE INSOLVENCY RESOLUTION PROCESS IN SHAPING INDIA’S SOCIO-ECONOMIC DEVELOPMENT: A LEGAL AND REGULATORY REVIEW - Kumar, Devesh; Das, Pradip Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This article underscores the crucial role of regulatory bodies in insolvency processes, providing the audience with a comprehensive understanding of their functions. They play a significant part in creating a conducive environment for restructuring viable businesses and rehabilitation. The Corporate Insolvency Resolution Process (CIRP) implementation under the Insolvency and Bankruptcy Code (IBC), 2016, has transformed the corporate insolvency regime of India and has affected the economic growth, wealth distribution, employment stability and ultimately socio-economic development of India. This paper evaluates the CIRP by scrutinising the legislative provisions and analysing case studies of various distressed companies to determine how far it has facilitated corporate distress resolution and protected the interests of its stakeholders. It focuses on the practical implementation of the CIRP and identifies the challenges in the CIRP, like judicial interpretation, procedural delays, and regulatory ambiguities. Ultimately, it provides suggestions for improving the efficiency and efficacy of insolvency resolution in India to promote sustainable socio-economic development, reassuring the audience of the regulatory bodies’ commitment to the process.